9n=6n+36

Simple and best practice solution for 9n=6n+36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9n=6n+36 equation:


Simplifying
9n = 6n + 36

Reorder the terms:
9n = 36 + 6n

Solving
9n = 36 + 6n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-6n' to each side of the equation.
9n + -6n = 36 + 6n + -6n

Combine like terms: 9n + -6n = 3n
3n = 36 + 6n + -6n

Combine like terms: 6n + -6n = 0
3n = 36 + 0
3n = 36

Divide each side by '3'.
n = 12

Simplifying
n = 12

See similar equations:

| 112y^2-9xy-x^2= | | 4y+7=y-14 | | 9x^2=100 | | 0.5(2+3.1*5.2)-3.71= | | Ln(10)=ln(x-1)-ln(18) | | 2-5(x-6)=x+12-8x | | 4-(x-3)=x+7 | | 8n-11=29 | | 2(90+-1y)+2y=180 | | 0.25x^2-x-2=0 | | 108y^2-3xy-x^2= | | 0=x^2-8x+4 | | 0.5x^2-x-10=0 | | 12c-5+15c+27= | | 8y^2-23y-3=0 | | 96y^2-22xy+x^2= | | Y=x^2-8x+4 | | m(m-2)=24 | | 5(3n+1)=7(6n+9)+2 | | x^2-2x-5=30 | | -22=n-16 | | 0.9x^2+5.4x-4=0 | | z-1=4(7z-4) | | 0=16x^2+8x+1 | | 5v+3=18 | | 3a(3a+2a-7)= | | 220=0,22.x | | w^2+2wj-35j^2= | | 3x^2+15x-3=0 | | 220=1,1.x | | x^2+9x-90= | | -12y-14=142 |

Equations solver categories